Implementation of Islamic Business Ethics on Merchant Behavior Sidoarjo Krempyang Traditional Market Chicken Eggs - Hersa Farida Qoriani (SAFE-Network, 2022)
Ethics is a polite attitude that must be owned by everyone in carrying out various activities, whether trading, teaching, asking questions, including in business we must also prioritize ethics. Ethics are attitudes, knowledge, morals that must be considered in organizing and managing a business. Attitudes that reflect ethics in trading or doing business include being honest, kind, respectful of others, indifferent, responsible, considerate, and so on. Pagerwojo is one of the villages where the majority of the population trades eggs. They usually have horen or free-range chicken farms close to where they live. So they usually sell their livestock chicken eggs to the Krempyang market around where they live. The focus of the problem here is how is the implementation of islamic business ethics in the behavior of chicken egg traders in Pagerwojo, Sidoarjo. The research method used is descriptive qualitative, which means research with a qualitative approach is a research procedure that produces descriptive data. The purpose of this research was to determine the implementation of business ethics in the behavior of chicken egg traders in the Krempyang market, Pagerwojo, Sidoarjo. This research discusses at length the stages of human awareness of the application of business ethics in their daily trade from an Islamic perspective. It takes time and process for the chicken egg traders in the Krempyang market to develop ethical awareness in trading or doing business. Related to how the implementation of business ethics in the behavior of chicken egg traders in the Krempyang market, pagerwojo, Sidoarjo. The results of the study show that, egg traders in the Krempyang market, Pagerwojo, Buduran, Sidoarjo have understood islamic business ethics, and have believed that Islamic teachings have regulated all human activities or activities, including in matters of trading or egg business, the sole purpose of which is to gain the blessings of Allah the creator. Egg traders have implemented the principles of Islamic business ethics, namely monotheism, balance, free will, responsibility, honesty, fairness, and so on.